Promoting effect of small molecules in cardiomyogenic and neurogenic differentiation of rat bone marrowderived mesenchymal stem cells - Ramin, Khanabdali; Anbarieh, Saadat; Maizatul Fazilah, Abd Razak; Khairul Fidaa', Khairul Bazli; Rida-e-Maria, Qazi; Ramla Sana, Khalid; Durriyyah Sharifah, Hasan Adli; Soheil Zorofchian, Moghadamtousi; Nadia, Naeem; Irfan, Khan; Asmat, Salim; Shamsul Azlin, Ahmad Shamsuddin; et al. (DRUG DESIGN, DEVELOPMENT AND THERAPY - DOVE PRESS, 2015)
Small molecules, growth factors, and cytokines have been used to induce differentiation of stem cells into different lineages. Similarly, demethylating agents can trigger differentiation in adult stem cells. Here, we investigated the in vitro differentiation of rat bone marrow mesenchymal stem cells (MSCs) into cardiomyocytes by a demethylating agent, zebularine, as well as neuronal-like cells by β-mercaptoethanol in a growth factor or cytokines-free media. Isolated bone marrow-derived MSCs cultured in Dulbecco’s Modified Eagle’s Medium exhibited a fibroblast-like morphology. These cells expressed positive markers for CD29, CD44, and CD117 and were negative for CD34 and CD45. After treatment with 1 µM zebularine for 24 hours, the MSCs formed myotube-like structures after 10 days in culture. Expression of cardiac-specific genes showed that treated MSCs expressed significantly higher levels of cardiac troponin-T, Nkx2.5, and GATA-4 compared with untreated cells. Immunocytochemical analysis showed that differentiated cells also expressed cardiac proteins, GATA-4, Nkx 2.5, and cardiac troponin-T. For neuronal differentiation, MSCs were treated with 1 and 10 mM β-mercaptoethanol overnight for 3 hours in complete and serum-free Dulbecco’s Modified Eagle’s Medium, respectively. Following overnight treatment, neuron-like cells with axonal and dendritic-like projections originating from the cell body toward the neighboring cells were observed in the culture. The mRNA expression of neuronal-specific markers, Map2, Nefl, Tau, and Nestin, was significantly higher, indicating that the treated cells differentiated into neuronal-like cells. Immunostaining showed that differentiated cells were positive for the neuronal markers Flk, Nef, Nestin, and β-tubulin.